Effect of metachronous primary and secondary solid cancers in patients with multiple myeloma: a retrospective study from a single-center - Ji, Yunfei; Li, Hujun; Zhang, Huanxin; Cheng, Hai; Wang, Ying; Xu, Kailin; Li, Zhenyu (Frontiers in Immunology, 2025)
Statement of translational relevanceEffects of metachronous primary malignant solid tumor (MPMST) on survival risk and prognosis of multiple myeloma (MM) and differences between MPMST occurring before and after MM remains unclear. Use of well-characterized clinical information of individual patient, we found that older patients with MM (≥ 65 years) had a higher risk of developing MPMST. Patients with MM and MPMST including male patients, aged ≥ 65 years and those with ISS stage III had a worse prognosis. The top three solid cancers occurred before and after MM were the lung, thyroid, and breast cancer. These findings provide detailed information for the precise treatment of patients with MM and MPMST.ObjectiveTo analyze the effects of MPMST on MM and the risk difference of MPMSTs occurring before and after MM.MethodsRetrospective data from patients with MM and MPMST, including sex, age, immunoglobulin isotype, ISS stage, and therapy, were collected from 2015 to 2023. Differences in variables, risk, and survival were compared using the χ² test, logistic regression analysis and the Cox model, respectively.ResultsThe 34 (1.57%) patients with MM and MPMST identified from a total of 2167 MM patients had a shorter overall survival. The survival risk was higher in male patients with MM and MPMST (HR: 3.96, 95% CI: 1.05 -14.96), in those aged ≥ 65 years (HR: 3.30, 95% CI: 1.41 -7.71), and with ISS stage III (HR: 4.08, 95% CI: 0.81-20.65). Patients with MM subsequent to CAR-T cell therapy had neither enhanced incidence rates of second solid cancers nor had longer overall survival time. Furthermore, the top three solid cancers occurred before or after MM were lung, thyroid, and breast cancer.ConclusionMale patients, aged ≥ 65 years and MM patients with ISS stage III and MPMST had a worse prognosis.